Kinetic investigations of oxidative roasting and afterwards leaching of copper-lead matte - Minić Duško; Petković Desimir; Štrbac N.; Mihajlović Ivan; Živković Živan D. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this paper, results of copper - lead matte investigations are presented. Investigated copper-lead matte is intermediate product of lead production in TREPCA-Zvecan. In the first part of the paper characterization of starting material is presented, consisting of: chemical composition analysis (XRQ), sceaning electron microscopy (SEM) and diffractometry (XRD). Thermal properties of matte investigated were determined using differential thermal analysis (DTA) at characteristic temperatures. Using results of induced analysis, mechanism of matte oxidation process was determined. In second part of the paper kinetic parameters describing oxidative roasting and afterwards leaching in sulfuric acid of copper-lead mate are presented.